Policing as a Profession in Social Media from a Comparative Perspective - Kriskó, Edina; Kovács, Ágnes (Magyar Rendészet, 2025)
The need for publicity, transparency and accountability has increased as a pressure on police forces since the emergence of social media. But while initially the novelty and lack of experience with new tools excused police forces from uncertainties, shortcomings or mistakes in managing their profiles, a quarter of a century later, the police can be accountable for awareness and usefulness of their practice. The main question of the research, based on social media monitoring, is how the different branches of policing, their specific activities and the content that highlights expertise and promotes and recognises policing to citizens are presented, beyond the organisational image-building function. The applied method is the qualitative document and text analysis supported by computer software to analyse the Facebook activity of the Hungarian Police and a Hungarian (community) police officer in Canada. The sample included two different months’ shared content for both profiles studied using purposive sampling. The results show a strong contrast in terms of the direct law enforcement implications of the content. Hungarian communication is centralised, highly controlled, organisational and professional, but at a great distance from the day-to-day tasks, while Canadian communication is personal, semi-professional-layman and gives a direct insight into the working day of the police. Our conclusion is that different policing models enable very different content along different practices, and the reasons are rooted in both regulation and culture. While the Hungarian legislation relegates the individual police officer to the background in order to strengthen the image of the organisation through propaganda, overseas it is the individual who brings the profession ‘in the flesh’ and gives it credibility and legitimacy.